(untitled) (JURNAL PROTEKSI KESEHATAN, 2025)
Turmeric oil is an essential oil extracted from Curcuma domestica rhizome, containing active compounds like turmerone, atlantone, and zingiberone, with various pharmacological activities. This study aimed to evaluate the antibacterial activity of turmeric oil nanoemulsion formulations (F1, F2, F3) against Staphylococcus aureus and Escherichia coli. The nanoemulsions were characterized for organoleptic properties, pH, viscosity, stability, homogeneity, droplet size, and zeta potential. All formulas appeared as thick, yellow, aromatic liquids with good homogeneity, pH of 6.8–7.0, and showed no separation upon centrifugation. Droplet sizes were 23.2 nm (F1), 203.8 nm (F2), and 298.7 nm (F3), with zeta potentials of –18.5 mV, –13.4 mV, and –8.5 mV, respectively. Antibacterial tests using the diffusion method showed moderate activity with inhibition zones ranging from 5.0–9.8 mm. These findings indicate that turmeric oil nanoemulsions are physically stable and exhibit moderate antibacterial activity.